2020
DOI: 10.2459/jcm.0000000000001058
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmic event prediction in patients with heart failure and reduced ejection fraction

Abstract: Aims Implantable cardioverter defibrillator (ICD) is an effective treatment to reduce mortality in patients with symptomatic heart failure and left ventricular ejection fraction (LVEF) 35% or less. LVEF presents a low sensitivity for predicting arrhythmic events. Aim of this study was to identify predictors of sustained ventricular arrhythmias (SVAs), overall and according to the cause of heart failure. Methods Single-center, retrospective, cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Our analysis also found that the fQRS patients were significantly 1.5 years older than non-fQRS patients and had a 12% increased incidence of diabetes. Multiple studies have shown that age is not a contributing factor to VA in ICD patients (Santangelo et al, 2021), (Bergau et al, 2017), and we and others have found that comorbidities are not often associated with VA or appropriate ICD therapy (Engstrom et al, 2020). While some studies have demonstrated a link between diabetes and VA (Grisanti, 2018), others have reported the opposite (Juhani Junttila et al, 2020), which may be related to HF…”
Section: Fqrs Is Associated With Ventricular Arrhythmias In Hf Patientsmentioning
confidence: 83%
“…Our analysis also found that the fQRS patients were significantly 1.5 years older than non-fQRS patients and had a 12% increased incidence of diabetes. Multiple studies have shown that age is not a contributing factor to VA in ICD patients (Santangelo et al, 2021), (Bergau et al, 2017), and we and others have found that comorbidities are not often associated with VA or appropriate ICD therapy (Engstrom et al, 2020). While some studies have demonstrated a link between diabetes and VA (Grisanti, 2018), others have reported the opposite (Juhani Junttila et al, 2020), which may be related to HF…”
Section: Fqrs Is Associated With Ventricular Arrhythmias In Hf Patientsmentioning
confidence: 83%
“…A simple clinical score, based on comorbidities and NYHA class, identifies patients with more benefits from ICD implantation. 58 In another cohort (n ¼ 497), at long-term follow-up (median time 70.4 months), 16.5% had received at least one appropriate shock (3.12%/year), whereas 15.1% had received at least one inappropriate shock.…”
Section: Medical Therapymentioning
confidence: 96%
“…In a single-centre, retrospective, cohort study including 193 patients (51 nonischemic and 142 ischemic) with chronic HF and LVEF < 35% who had received ICD for primary prevention of sudden cardiac death, 32 (16.2%) patients presented sustained ventricular arrhythmias during a median follow-up of 1440 days. A simple clinical score, based on comorbidities and NYHA class, identifies patients with more benefits from ICD implantation 58 . In another cohort ( n = 497), at long-term follow-up (median time 70.4 months), 16.5% had received at least one appropriate shock (3.12%/year), whereas 15.1% had received at least one inappropriate shock.…”
Section: Devices and Telemonitoringmentioning
confidence: 99%
See 2 more Smart Citations